2021
DOI: 10.5223/pghn.2021.24.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Pyloric Stenosis: 10 Years' Experience with Standard Open and Laparoscopic Approach

Abstract: Purpose Hypertrophic pyloric stenosis (HPS) is the most common cause of gastric obstruction in newborns. Extra-mucosal pyloromyotomy can be performed through a small laparotomy or laparoscopy. The aim of this study was to compare the two surgical techniques. We also analyzed the incidence of HPS in infants in the last 10 years in relation to the demographic trend of our province. Methods We analyzed all the cases of HPS treated at our Unit between January 2010 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
1
8
1
8
Order By: Relevance
“…Various pediatric procedures such as hernia repair, varicocelectomy, cholecystectomy, appendectomy, pyloromyotomy etc., which until then had been performed exclusively by the open approach, began to be performed using laparoscopic approach [15][16][17][18][19][20][21][25][26][27][28][29]. Numerous studies reported benefits of laparoscopic approach for treatment of hypertrophic pyloric stenosis such as faster recovery, faster postoperative feeding, lesser pain, shorter surgical and hospitalization times and lower incidence of wound related complications [6,11,[15][16][17][18][19][20][21][22]. The cosmetic results are incomparably better in infants operated using laparoscopic approach [6,11,[15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various pediatric procedures such as hernia repair, varicocelectomy, cholecystectomy, appendectomy, pyloromyotomy etc., which until then had been performed exclusively by the open approach, began to be performed using laparoscopic approach [15][16][17][18][19][20][21][25][26][27][28][29]. Numerous studies reported benefits of laparoscopic approach for treatment of hypertrophic pyloric stenosis such as faster recovery, faster postoperative feeding, lesser pain, shorter surgical and hospitalization times and lower incidence of wound related complications [6,11,[15][16][17][18][19][20][21][22]. The cosmetic results are incomparably better in infants operated using laparoscopic approach [6,11,[15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with breakthrough of laparoscopic surgery among the pediatric surgeons laparoscopic pyloromyotomy has been more frequently used due to its benefits, such as significantly lesser duration of surgery, faster oral intake, faster recovery, lesser pain and tissue trauma, and excellent cosmetic effects [6,11,[15][16][17][18]. In regards to efficacy of the procedure a meta-analysis confirmed that laparoscopic approach had the same safety and efficacy as open surgery [15].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations